INVESTIGATION OF LEAD DISTRIBUTION IN GUNSHOT RESIDUES BY THE X-RAY FLUORESCENCE ANALYSIS METHOD - DOTSENKO, OLEH; SHELESTIUK, OLEKSANDR; ANTONIUK, OLEKSANDR; STREMETSKYI, OLEKSANDR (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The study investigates the dependence of the intensity of lead X-ray spectral lines in gunshot residues on the shooting distance and their radial distribution on the target surface. Artificial intelligence methods were employed for modeling, while the obtained experimental data were processed and analyzed. Modeling of the propellant gas jet propagation made it possible to estimate the distance at which an intensive transfer of gunshot residues occurs, which was found to be less than 50 cm and was experimentally confirmed. The qualitative model of lead distribution in gunshot residues generally agrees with the experimental results. A significant qualitative difference was established between the experimental data of lead X-ray line intensities and the relative concentration obtained along the shooting axis compared to other radial positions. This difference is explained by the transport of gunshot residues along the bullet surface, which is not accounted for in the model. A regularity in the distribution of lead in gunshot residues from a .22 LR cartridge was found, depending on both the distance to the target and its radial distribution on the target, which can be determined by measuring the intensity of lead X-ray emission lines. It has been shown that the Elvax Pro X-ray fluorescence spectrometer can be used to study gunshot residues and to determine the distribution pattern of lead depending on the shooting distance and its radial distribution on the target, which has potential significance for forensic examinations and ballistic investigations. Once the dependence of the lead emission intensity on the shooting distance and radial distribution on the target has been experimentally established, it becomes possible to determine the distance from which the shot was fired.
Keywords: gunshot residues; X-ray fluorescence analysis; lead; propellant gas jet; modeling; Elvax Pro; shooting distance